Habitat Use and Survival of the Spoted Tinamou (Nothura maculosa) in Agroecosystems in the Province of Buenos Aires, Argentina - Jeffrey J. Thompson; John P. Carroll (National Quail Symposium Proceedings, 2017)
Changes in the composition and configuration of agricultural landscapes stemming from grassland conversion and agricultural intensification have contributed to the global declines of many grassland and shrubland birds. In both North America and Europe there exists a large body of research on the effects of agriculture on populations of terrestrial gamebirds. However, little research exists for these species in Argentina or Latin America in general. In Argentina the most important gamebird species is the spotted tinamou (Nothura maculosa). This species has become increasingly scarce in a significant portion of its range, possibly due to agricultural intensification over the last 15 years. Using radio telemetry, we examined habitat use, movements, and survival of spotted tinamous in 2 landscapes in the province of Buenos Aires, Argentina; one dominated by annual row crops and the other used for annual crops and grazing. During winter, individuals used in order of preference: fallow fields and areas with short herbaceous vegetation, followed by wetlands. Areas in winter wheat and field edges were used least in relation to their availabilty. Although birds generally maintained small home ranges, in some cases changes in cattle density and the structure of row crops caused birds to move considerable distances. Survival mid-winter to early spring was more than double in the mixed landscape (s ̂ = 0.73, SE = 0.19) compared with the landscape dedicated to row crops (s ̂ = 0.33, SE = 0.19). Considering how research in other parts of the world has demonstrated the effects of agricultural intensification on terrestrial gamebirds, these results are not unexpected and suggest a precarious future for the conservation of grassland and agroecosystem species in Argentina in light of present agricultural trends.
Keywords: agricultural intensification; conservation; Nothura maculosa; spotted tinamou; survival